The investigation of activated carbon by K2CO3 activation: Micropores- and macropores-dominated structure. (July 2022) - Khuong, Duy Anh; Trinh, Kieu Trang; Nakaoka, Yu; Tsubota, Toshiki; Tashima, Daisuke; Nguyen, Hong Nam; Tanaka, Daisaku
Abstract: In this study, the K2 CO3 activation of bamboo was investigated in detail, and the structure and properties of the prepared activated carbons were tested for the feasibility of CO2 capture application and the potential for both ion and bacteria adsorption for use in the field of hazardous wastewater treatment. Activated carbons were produced with different activator ratios, from 0.5 to 6 according to the sample mass ratio. The ratio of H or O to C (H/C or O/C) increased with the increasing amount of K2 CO3 added for the activation. The samples had a highly-porous microporous structure, in which the micropore volume was calculated to be 0.6 cm 3  g −1 by the DR method of the CO2 adsorption isotherm at 298 K. The BET surface area and total pore volume estimated from the N2 adsorption isotherms at 77 K of the activated materials increased according to the increase of the K2 CO3 impregnation ratio to a maximum value of 1802 m 2  g −1 and 0.91 cm 3  g −1, respectively. Moreover, the K2 CO3 -activated samples had a specific morphology, that is, macropores which are presumed to be derived from bubbles. The X-ray-CT images showed that the bubble-like structure is not only on the surface but also inside the samples. The results of gas adsorption methods, mercury porosimetry, and SEM showed the co-existence of micropores (<2 nm) and macropores (100–10, 000 nm). The results highlighted the unique pore structure, that is, the coexistence of micropores and macropores that would contribute to forming solutions for carbon sequestration in the atmosphere and wastewater treatment. Graphical abstract: Image 1 Highlights: The combination of micropores and macropores was recognized in K2 CO3 -activated bamboo. The special morphology was found as the bubble-like surface texture. K2 CO3 -activated carbon was feasible for CO2 adsorption application. The prepared samples were found to have a high potential for water treatment.